L-PRF associado ao enxerto gengival livre no “creeping attachment”: Estudo clínico randomizado. - Alves, Breno Edson Sendão [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The main objective of the present clinic study will be to evaluate through observation of the root covering, the “creeping attachment” (CA) on Miller class II gingival recession treated with free gingival graft combined with leucocyte and platelet rich -fib rin (PRF-L). 12 patients with bilateral Miller Class II gingival recession in lower premolars were recruited . Group FGG (n= 12): control group, the site will receive the root coverage with free gingival graft, and Group FGG/L-PRF (n= 12): will be performed an association between free gingival graft and L-PRF, the L- PRF membrane stabilized to the receptor region and suturing the EGL. To obtain this platelet concentrate, 20 ml of blood of each patient will be collected and immediately centrifuged at 2700rpm for 12 minutes. The following parameters illbe measured: O`Leary plaque index, gingival index, eight of gingival recession, recession width, amount of eratinized mucosa, probing depth (PD) and then, the linical attachment level will be conducted. The measurements will be performed at 30, 90, 180 e 60 days after the surgical procedure . The CA will be measured at 90, 180 and 360 days. Data will be analyzed statistically (p < 0.05) in a specialized omputer program (Bioestat 5.0). After 360 days, ignifica nt differences were not found between the wo roups for CA, however there was a significant difference for keratinized gingiva, gingival height and linical attachment level. EGL and EGL/L -PRF are qually successful in the cree ping attachment gain in gingival recession of Miller class II.

O propósito do presente estudo clínico será avaliar o efeito do tratamento de recessões gengivais classe II de Miller com enxerto gengival livre (EGL), associado a fibrina rica em plaquetas e leucócitos (L-PRF) no “creeping attachement” (CA). 12 pacientes que apresentavam recessões bilaterais classe II de Miller, localizadas em pré-molares inferiores, totalizando 24 sítios, foram divididos aleatoriamente nos Grupo EGL (n=12), é o grupo controle no qual o sitio recebeu o recobrimento radicular com enxerto gengival livre (EGL); e o Grupo EGL/L-PRF (n=12), EGL associado ao L-PRF, estabilização de membrana de L-PRF no leito receptor e sutura do EGL. Para obtenção do L-PRF, foi realizada a coleta de 20 ml de sangue de cada paciente, que foi imediatamente centrifugado a 2700 rpm, por 12 minutos. Realizou a medida do recobrimento radicular o presente no período inicial e após 30 dias de pós-operatório, e foi avaliado a quantidade de CA (90, 180 e 360 dias). Após 360 dias não foi possível observar uma diferença significativa de CA entre os grupos EGL (1.81 ± 0.40) e 1.00 ± 0.70 (EGL/L-PRF ), entretanto ocorreu diferença na quantidade de mucosa queratinizada, gengiva inserida e altura da recessão. EGL e EGL/L-PRF proporcionaram aumento na mucosa queratinizada e migração tecidual em recessões classe II de Miller.
L-PRF associated with free gingival graft in the “creeping attachment”: Randomized clinical trial.
Keywords: Gingivoplasty; Fibrina rica em plaquetas; Retração gengival; Gengivoplastia